Analyzing the Factors Affecting the Price of Broiler Chicken in Turkey Using the Boosting Regression Method - Arikan, M. S.; Cevrimli, M. B.; Polat, M.; Mat, B.; Akin, A. C.; Ozel, Z.; Tekindal, M. A. (Facta-Fundacio Arnco Ciencia Tecnologia Avicolas, 2022)
Investigating the factors that affect broiler chicken prices in Turkey is vital for understanding market formation. The parameters and factors likely to influence the price of broiler chicken were analyzed for the period between 2010-2020 in Turkey. The study adopted the boosting regression model to predict the correlation between broiler chicken consumer price and variable factors like broiler feed, corn, soybean meal, wheat prices, the dollar exchange rate, producer price index (PPI), and agricultural PPI. The accuracy of the estimation of the regression model created according to the results of the analysis was calculated as 86%. The producer price index variable caused the highest relative impact (25.63%) on broiler chicken meat prices. The highest positive correlation was obtained between the producer price index and the agricultural PPI (r = 0.984). Thus, it was determined that chicken prices were affected by feed raw material prices and the general economic conditions in Turkey. In addition to improving the prevailing economic conditions, an effective price control mechanism is required to prevent excessive price fluctuations in the sector. Simultaneously, it is essential to create policies to reduce input costs.
Keywords: Chicken meat; price; boosting regression; Turkey